Targeting ferroptosis as novel therapeutic approaches for epilepsy - Jin, Yuzi; Ren, Lei; Jing, Xiaoqing; Wang, Hongquan (Frontiers in Pharmacology, 2023)
Epilepsy is a chronic disorder of the central nervous system (CNS) characterized by recurrent unprovoked seizures resulting from excessive synchronous discharge of neurons in the brain. As one of the most common complications of many neurological diseases, epilepsy is an expensive and complex global public health issue that is often accompanied by neurobehavioral comorbidities, such as abnormalities in cognition, psychiatric status, and social-adaptive behaviors. Recurrent or prolonged seizures can result in neuronal damage and cell death; however, the molecular mechanisms underlying the epilepsy-induced damage to neurons remain unclear. Ferroptosis, a novel type of regulated cell death (RCD) characterized by iron-dependent lipid peroxidation, is involved in the pathophysiological progression of epilepsy. Emerging studies have demonstrated pharmacologically inhibiting ferroptosis can mitigate neuronal damage in epilepsy. In this review, we briefly describe the core molecular mechanisms of ferroptosis and the roles they play in contributing to epilepsy, highlight emerging compounds that can inhibit ferroptosis to treat epilepsy and associated neurobehavioral comorbidities, and outline their pharmacological beneficial effects. The current review suggests inhibiting ferroptosis as a therapeutic target for epilepsy and associated neurobehavioral comorbidities.